Peran Pemerintah dalam Pengelolaan Zakat Menurut Abu Ubaid Al Qasim (Studi Kasus Kota Pontianak) - Romi Suradi; Bustami Bustami (Jurnal Ilmiah Ekonomi Islam, 2022)
The management of zakat at this time has not implemented the pattern and system of withdrawal, management and distribution as a whole as stated in the Regional Regulation of Pontianak City No. 25 of 2002 concerning Guidelines for the Management of Pontianak City Zakat. Abu Ubaid Al-Qasim Bin Salam gave new thoughts and perspectives on the government's role in zakat management, including the management of zakat - zakat other than zakat assets that can be taken forcibly if not fulfilled. Thus making the government as the sole executor and punisher. Regarding the distribution of excess use of zakat funds, it can be transferred to other areas, not just for business development that has been carried out as it is now. This research uses literature study research. The type of data used is secondary data, namely data obtained indirectly. The data needed in this study were taken from documents related to research. The data analysis technique used was descriptive analytic which was sourced from the discussion in the Kitab al-Amwal by Abu Ubaid al-Qasim and its relation to the role of the government, especially the Pontianak city government.